Kinetic study of a change in intracellular ATP level associated with aerobic catabolism of ethanol by Streptococcus mutans. - Fukui, K (1988)
Streptococcus mutans, a group of lactic acid bacteria and a normal inhabitant of the human oral cavity, generates ATP by substrate-level phosphorylation coupled to oxidation of ethanol (an end product of fermentation of sugars) into acetate in the presence of oxygen (K. Fukui, K. Kato, Kodama, H. Ohta, T. Shima moto, and T. Shimono, Proc. Jpn. Acad. 64B:13-16, 1988). Kinetic measurements were made of the cellular responses of S. mutans FA-1 to ethanol in comparison with those to glucose. In contrast to oxygen-independent acid production from glucose, oxygen was absolutely required for acid production from ethanol. Ethanol elicited a marked increase in the intracellular ATP concentration (ATPi) from a starved level to a steady level which was held constant as long as oxygen was present in the medium. Once oxygen was exhausted, ATPi returned to the starved level without delay. On the contrary, ATPi changes induced by glucose, which were independent of oxygen, followed a rather complicated time course before a steady level was established. Both the steady ATPi and the rate of accompanying oxygen consumption were functions of the ethanol concentration. These two parameters were linearly correlated, indicating that the unimolecular ATP turnover rate, which is independent of the rate of ATP generation in the steady state, can be calculated for cells energized by ethanol. The estimated turnover rate was 1.5 s-1 at 37 degrees C, which is comparable to that for other bacteria energized by glucose under nongrowing conditions.